2017
DOI: 10.1186/s12974-017-0925-3
|View full text |Cite
|
Sign up to set email alerts
|

microRNA dysregulation in polyglutamine toxicity of TATA-box binding protein is mediated through STAT1 in mouse neuronal cells

Abstract: BackgroundPolyglutamine diseases constitute a class of neurodegenerative disorders associated with expansion of the cytosine-adenine-guanine (CAG) triplet, in protein coding genes. Expansion of a polyglutamine tract in the N-terminal of TBP is the causal mutation in SCA17. Brain sections of patients with spinocerebellar ataxia 17 (SCA17), a type of neurodegenerative disease, have been reported to contain protein aggregates of TATA-binding protein (TBP). It is also implicated in other neurodegenerative diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
(47 reference statements)
0
12
0
Order By: Relevance
“…We have previously shown that neuronal cells expressing toxic 59Q-TBP protein induce aberrant interferon signaling resulting in Stat1 mediated upregulation of interferon-stimulated genes (ISGs) 27 . In the tetracyclineinduced cell lines used in the study, we verified that STAT1 protein is induced and activated by phosphorylation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that neuronal cells expressing toxic 59Q-TBP protein induce aberrant interferon signaling resulting in Stat1 mediated upregulation of interferon-stimulated genes (ISGs) 27 . In the tetracyclineinduced cell lines used in the study, we verified that STAT1 protein is induced and activated by phosphorylation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we have shown that miR-29a/b targets VDAC1 as well as BACE1, preventing apoptosis in the neuronal cells 25 and ataxia in mice 26 . Recently, we showed that interferon signaling is elevated in this cellular model of SCA17, prompting the hypothesis that intercellular signaling leading to bystander cell death may aggravate the pathology of the disease 27 . Here, we explored the response of neuronal cells to CAG repeat RNA, specifically testing if CAG repeat RNA mediated toxicity was sufficient to explain the aberrant interferon signaling and cell death seen in polyQ expressing neuronal cells.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…SCA17 is caused by the expansion of a repeated Poly Q in the TBP gene and is characterized by intranuclear protein aggregation and selective loss of cerebellar neurons (Roshan et al, 2017). MiR-29a/b has been found down-regulation in a SCA17 cellular model by qRT PCR.…”
Section: Mirna In Poly Q Diseasementioning
confidence: 99%
“…1. It has been suggested that trinucleotide repeat expansion in the CAG in protein coding regions in the genome may cause polyglutamine (polyQ) disease, which induces a set of dominantly inherited neurodegenerative disorders including Huntington's disease (HD), spinocerebellar ataxia, type 1/2/3/6/7 (SCA-1/2/3/6/7), dentatorubropallidoluysian atrophy (DRPLA), Machado-Joseph disease (MJD) and spinobulbar muscularatrophy (8,9).…”
Section: Introductionmentioning
confidence: 99%